2001
DOI: 10.1016/s0022-2275(20)31681-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the apolipoprotein A-IV Q360H polymorphism on postprandial plasma triglyceride clearance

Abstract: Apolipoprotein (apo)A-IV is synthesized in the small intestine during fat absorption and is incorporated onto the surface of nascent chylomicrons. In circulation, apoA-IV is displaced from the chylomicron surface by high density lipoprotein-associated C and E apolipoproteins; this exchange is critical for activation of lipoprotein lipase and chylomicron remnant clearance. The variant allele A-IV-2 encodes a Q360H polymorphism that increases the lipid affinity of the apoA-IV-2 isoprotein. We hypothesized that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Several human protein-coding SNPs of APOA4 have been associated with clinical phenotypes, which includes the N147S variant detected in this study that is associated with the response to fenofibrate treatment . Another phenotype associated with several APOA4 variants is altered plasma total triacylglycerol abundance, , which is in agreement with our correlation analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Several human protein-coding SNPs of APOA4 have been associated with clinical phenotypes, which includes the N147S variant detected in this study that is associated with the response to fenofibrate treatment . Another phenotype associated with several APOA4 variants is altered plasma total triacylglycerol abundance, , which is in agreement with our correlation analysis.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, our sample is an admixed population from Brazil and His-allele has been proposed as a marker of European admixture 41 ; hence, it could be modifying our results. Concerning serum levels, we observed that 360His allele showed reduced HDL and higher VLDL and TG levels, which might be due to delayed postprandial clearance of TG-rich lipoprotein 42 and may be a risk factor for metabolic disease.…”
Section: Discussionmentioning
confidence: 80%
“…Common APOA4 mutations include N147S, T347S, and Q360H [ 83 ]. A study by Hockey et al showed that the 360H allele has greater lipid affinity compared with 360Q [ 84 ]. APOA4 also has an anti-atherosclerotic effect.…”
Section: Apoa4: Biomarker For Disorders Of Lipid Metabolismmentioning
confidence: 99%